REGRESSION ANALYSIS ALGORITHM FOR THE RESULTS OF REINFORCED CONCRETE SLABS TECHNICAL INSPECTION - Mikhailov, Valentin; Akhmediev, Serik; Tazhenova, Gulzada; Karacasu, Murat; Tokanov, Daniyar; Bakirov, Madi (Journal of Applied Engineering Science, 2025)
The paper presents an algorithm for calculating key statistical parameters, including correlation dependences, correlation coefficients, and a method of checking the presence of a linear dependence. A quadratic regression equation is obtained, regression curve graphs are constructed, distribution functions and probability densities with the procedure for their normalization are calculated. The main statistical parameters of random variables are also calculated: mathematical expectation, variance, standard deviation, and quantiles of various levels. The proposed regression analysis algorithm can be used to assess safety and reliability of building structures, which allows analyzing their operation in a probabilistic form. Based on the theoretical and applied results of the work, prospects are opened for further development of probabilistic analysis methods for safety of construction projects as a whole, taking into account their complex structure and interaction of various structural elements.